Mechanisms and reaction conditions of CO2 with o-aminobenzonitrile for the synthesis of quinazoline-2, 4-dione. Issue 51 (September 2021) - Wang, Zhaoyang; Xie, Ruijun; Hong, Hailong; Han, Limin; Zhu, Ning
Graphical abstract: Highlights: This review summarized the formation mechanism of quinazolindione from the reaction of CO2 and o-aminobenzonitrile. We discussed the reaction medium, catalyst and reaction temperature that influence the reaction pathways of o-aminobenzonitrile with CO2 . This review systematically clarified the reason why the amino group or the nitrile group of o-aminobenzonitrile firstly react with CO2 . Abstract: Quinazoline-2, 4(1H, 3H)-dione derivatives are key intermediates in pharmaceutical, biological and chemical fields. To avoid the use of toxic carbonylation reagents such as phosgene, carbon monoxide and potassium cyanate, green synthesis methods for preparing quinazolindiones via the reaction of o-aminobenzonitrile with CO2 are developed. In this review, the factors such as reaction medium, catalyst and reaction temperature that influence the reaction of o-aminobenzonitrile with CO2 are systematically discussed. The protic solvent is favorable for the nitrile group as the initial reaction site to react with CO2 . In contrast, the reactivity of the nitrile group and amino group of o-aminobenzonitrile could hardly be affected by aprotic solvent. Moreover, the reaction is also strongly affected by the catalyst, which is evaluated by the basicity and nucleophilicity of the catalyst. Specifically, the basicity mainly affects the activation of the amino group in the o-aminobenzonitrile substrate, whereas the nucleophilicity primarily impacts the formation of the CO2 activated state. The similarities and differences of different catalysts such as organic bases, inorganic bases, ionic liquids and supported catalysts in specific reaction pathways are also discussed in this review. In addition, the formation of isocyanate intermediate in the rearrangement process is significantly affected by the reaction temperature. The quinazolindione could be easily formed from the isocyanate intermediate, isomerized from the cyclic carbamate, under high reaction temperature. Furthermore, the quinazolindione could be formed directly by the isomerized cyclic carbamate under low reaction temperature.